BEHAVIOR ANALYSIS OF UMKM IN INDONESIA IN USING FINTECH LENDING (COMPARATIVE STUDY BETWEEN SHARIA FINTECH LENDING AND CONVENTIONAL FINTECH LENDING - Imsar; Nurbaiti; Siti Aisyah (RADJA PUBLIKA, 2023)
This study aims to examine how the behavior of Muslim SMEs in Indonesia towards the use of fintech lending. This study compares the acceptance of Muslim MSMEs towards fintech lending with sharia principles and conventional fintech lending. Researchers use the UTAUT 2 (Unified Theory of Acceptance and Use of Technology) approach, to find out the factors / determinations of fintech, especially peer to lending. The analytical method of the UTAUT 2 research model used by the authors in this study uses quantitative methods to measure user acceptance of peer to peer fintech and test hypotheses about the factors that influence user acceptance of peer to peer fintech codes. By using a quantitative approach, methods of collecting and analyzing data are needed to complete this research. Data collection was carried out by conducting a questionnaire survey and data analysis using path analysis for statistical analysis with PLS-SEM. The results of this study state that of the 12 variables, some have a positive and significant effect and some have no effect on the use of fintech lending application services for Muslim MSMEs in Indonesia. Then Fintech Lending Syariah has been used by MSMEs in Indonesia, but has not been able to dominate because there are still many Muslim MSMEs in Indonesia who are not aware of the existence of sharia services in fintech lending applications. Sharia Fintech Lending in Indonesia must increase the frequency,